Analysis of Village Fund Supervision in Gampong Geulumpang Tujoh, Matangkuli District (Study at the Inspectorate of North Aceh Regency) - Kurniawan, Rudi; Junaidi, Junaidi; Muhammad, Muhammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2020)
Supervision of village funds is an action in the management of village funds carried out by government officials. This is because village funds are funds sourced from the State Revenue and Expenditure Budget intended for villages through the Regency / City Regional Revenue and Expenditure Budget and are used to finance government administration, development and community and community empowerment. The purpose of this study was to determine the supervision of village funds carried out by the Inspectorate at Gampong Geulumpang Tujoh, North Aceh Regency. The type of research is using a qualitative approach. Data analysis used data reduction, data presentation and drawing conclusions or verification. The results of this study were the supervision of village funds carried out by the Inspectorate at Gampong Geulumpang Tujoh, Matangkuli District, North Aceh Regency, carried out in several stages, namely inherent supervision, functional supervision, legislative supervision and community supervision and the obstacles faced by the inspectorate in monitoring village funds in Gampong. Geulumpang Tujoh, Matangkuli District, North Aceh Regency, is that there is no element of accuracy of village funds, is not timely in providing village fund information and is not objective in managing village funds. It is hoped that the obstacles in the supervision of village funds carried out by the Inspectorate of North Aceh Regency should require a special budget provided by the central government to further support the implementation of supervision of village funds carried out by the North Aceh District inspectorate, besides that the North Aceh Inspectorate needs to add members to each supervisory team so that the inspection can run thoroughly.